Comprehensive analysis of dural ectasia in 150 patients with a causative FBN1 mutation. (23rd September 2013) - Sheikhzadeh, S.; Sondermann, C.; Rybczynski, M.; Habermann, C.R.; Brockstaedt, L.; Keyser, B.; Kaemmerer, H.; Mir, T.; Staebler, A.; Robinson, P.N.; Kutsche, K.; Berger, J.; et al.
<x xml:space="preserve">Abstract</x> The purpose of this study was to perform a comprehensive study of dural ectasia (DE) related to FBN1 mutations. We performed a database analysis of two German metropolitan regions of 150 patients (68 men, 82 women; mean age 35 ± 16 years). All patients had a FBN1 mutation and underwent dural magnetic resonance imaging. Age was <16 years in 20, 16–25 in 27, 26–35 in 67, and >35 in 36 patients. Prevalence of dural ectasia was 89% with criteria of Oosterhof and Habermann, 83% with Fattori, 78% with Lundby, and 59% with Ahn. DE was less frequent in patients <16 years with Ahn and Fattori. DE related to skeletal manifestations with all criteria, to aortic Z‐scores and mitral valve prolapse with criteria of Habermann and Lundby, and to age with criteria of Fattori. The Fattori‐grade of DE increased with age, aortic Z‐scores, and skeletal score points. There was no consistent relationship of DE with any type of FBN1 mutation. DE is frequent in patients with FBN1 mutations irrespective of age and its severity increases during life. Criteria of Oosterhof and Habermann yielded most consistent diagnostic results. DE relates to skeletal involvement, aortic Z‐scores, and mitral valve prolapse.